2023
DOI: 10.1111/aogs.14599
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of pregnant and lactating persons from breast cancer clinical trials: a review of active trials registered on ClinicalTrials.gov

Abstract: IntroductionTreatment of pregnancy‐associated breast cancer is complex, as providers try to balance risks to the pregnant person and the developing fetus. Given increased case fatality and increasing incidence, there is a pressing need understand the efficacy and safety of different treatment regimens in this population; however, pregnant and lactating people have traditionally been excluded from participating in randomized controlled trials (RCTs). Given recent efforts to expand the inclusion criteria for onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore systematic reviews and meta-analysis are also needed, which is well illustrated in the studies by Marasciulo et al, 9 and Zhang et al, 10 in this special issue. Importantly, as noted in the study reported by Metcalfe et al, 11 the systematic exclusion of pregnant and lactating patients from clinical trials has largely contributed to maintainance of evidence gaps on how best to treat these patients. The reason for excluding pregnant and lactating patients from studies appears to be the fear of research-related risks, which is currently a significant barrier to finding the best treatment approach to protect these patients from further complications.…”
Section: E D I T O R I a L The Challenges Of Cancer During Pregnancymentioning
confidence: 99%
“…Therefore systematic reviews and meta-analysis are also needed, which is well illustrated in the studies by Marasciulo et al, 9 and Zhang et al, 10 in this special issue. Importantly, as noted in the study reported by Metcalfe et al, 11 the systematic exclusion of pregnant and lactating patients from clinical trials has largely contributed to maintainance of evidence gaps on how best to treat these patients. The reason for excluding pregnant and lactating patients from studies appears to be the fear of research-related risks, which is currently a significant barrier to finding the best treatment approach to protect these patients from further complications.…”
Section: E D I T O R I a L The Challenges Of Cancer During Pregnancymentioning
confidence: 99%
“…Interestingly, almost one‐fourth of behavioral studies excluded patients with PrBC. 9 This systematic exclusion creates an unfortunate knowledge gap on the treatment approach to PrBC and pertinent issues such as timing of chemotherapy, effect of pregnancy on pharmacokinetics, harmful effects of radiation therapy delivered with modern methods, and use of certain cytotoxic drugs and novel targeted agents are still largely unclear. Therefore, instead of evidence‐based guidelines, management of PrBC is guided by expert consensus statements such as one recently published by the European Society for Medical Oncology.…”
Section: Introduction and Diagnosismentioning
confidence: 99%
“…The increased risk of mortality for cancers diagnosed during pregnancy and postpartum observed in our study and others is an area of concern that could relate to underlying differences in biology, delays in diagnosis, and delays in treatment. As pregnant and lactating people with cancer are rarely included in randomized clinical trials, optimal treatment strategies for this complex group of patients are unclear.…”
mentioning
confidence: 99%